Pelanggaran Etika Profesi serta Konsekuensi Tanggung Jawab Hukum dalam Kasus Suap Jaksa Farizal - Purnama, Rendika; Delzanty, Kayla; Talitha, Raisyha; Hakim, Mohammad Akmal Taris; Rosdiana, Hani; Ramadhani, Sherlyta; Permana, Fatur Rezqy; M, Mulyadi (Media Hukum Indonesia (MHI), 2025)
The bribery case involving Prosecutor Farizal represents the damaging impact of violations of professional ethics on the legitimacy of judicial institutions. The act is not only a violation of fundamental principles such as integrity and impartiality that should be upheld by every prosecutor, but also tarnishes the main values in Tri Krama Adhyaksa which are the moral foundation of the Indonesian Attorney General's Office. Farizal's involvement in corrupt practices also adds to the long list of cases of irregularities committed by law enforcement officers, thus deepening the crisis of public trust in the judicial mechanism in Indonesia. This study uses a normative legal method that relies on various written legal sources to answer the problems that have been formulated. The approach used in this study consists of a statutory regulatory approach and a case approach. Through the statutory regulatory approach, researchers examine relevant legal norms, especially those regulating the ethics of the prosecutor's profession and the form of legal accountability for violations committed by law enforcement officers. The results of the study show that the violation of professional ethics committed by Prosecutor Farizal in this bribery case reflects serious deviations that not only damage the integrity of the prosecutor's office, but also reduce public trust in the justice system. His actions, which involved accepting bribes to influence the legal process, are contrary to the basic principles of the Prosecutor's Code of Ethics and Code of Conduct, such as integrity, impartiality, and accountability.